The Role of Translation in the Development of Scientific Knowledge in the Premodern Islamic World - Khalid Hussain Mir; Md. Rafique Anjum (MAQOLAT: Journal of Islamic Studies, 2025)
This paper examines the profound impact of the translation movement on the development of scientific knowledge in the premodern Islamic world, focusing on the Abbasid Caliphate (8th to 10th centuries). The establishment of the "Bayt al-Hikmah" (House of Wisdom) in Baghdad under Caliph Al-Ma'mun (d. 933) played a crucial role in transferring scientific and philosophical knowledge from Greek, Persian, and Indian sources into Arabic. These translations went beyond mere replication; Islamic scholars engaged critically with the source material, adding commentaries and introducing refinements. This dynamic intellectual activity led to significant advancements in key scientific disciplines, including astronomy, medicine, and mathematics. In astronomy, the translation of Ptolemy’s "Almagest" helped shape Islamic astronomical thought, leading to advancements by scholars such as Al-Battani (d. 929) and Ibn al-Haytham (d. 1040). In medicine, the translation of the "Corpus Hippocraticum" and Galen's works provided the foundation for a comprehensive Islamic medical tradition, with Ibn Sina’s (d. 1037) "The Canon of Medicine" becoming a seminal text for centuries. In mathematics, the translation of Brahmagupta’s "Brahmasphuta Siddhanta" by Al-Khwarizmi (d. 850) revolutionized algebra and influenced global mathematical thought. The translation movement catalyzed intellectual growth, fostering cross-cultural exchanges that shaped both Islamic and global intellectual traditions. This paper highlights the essential role of multilingualism and translation in preserving, expanding, and disseminating scientific knowledge across cultures.